PEMBINAAN AKHLAK SISWA MELALUI KEGIATAN EKSTRAKURIKULER BADAN DAKWAH ISLAM MAN 1 KOTA MALANG - Hesti Dwi Rahayu; Muhammad Hanif; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Moral development has a function in an effort to prevent negative impacts arising from the current development. Time has changed the lifestyle of students. Starting from the decline in social life ethics and moral ethics. To correct these problems, there needs to be an effective effort to develop student morale in schools. One of them is through religious activities held at school, namely the Islamic Da'wah extracurricular activities that have been carried out at MAN 1 Malang City. Although the Islamic Da'wah extracurricular activities have been carried out, it does not rule out the possibility that not all students want to participate fully in this activity. The method used in this research is to use a qualitative research approach and type of case study research. Data collection techniques using participant observation, using unstructured interview methods and using the documentation method. The results showed that the morals of students in MAN 1 Malang city as a whole had good morals, although some others still showed bad behavior. This can be improved through activities carried out by Islamic da'wah bodies which are the focal point of religious activities in MAN 1 Malang city, with the hope of realizing intelligent learners in science that are also accompanied by noble morals. Keywords: Moral Development, Extracurricular Activities, Islamic Da’wah Agency